1999
DOI: 10.1038/sj.bjp.0702737
|View full text |Cite
|
Sign up to set email alerts
|

L‐NAME inhibits Mg2+‐induced rat aortic relaxation in the absence of endothelium

Abstract: 1 L-N G -nitro-arginine methyl ester (L-NAME; 100 mM), a nitric oxide synthase (NOS) inhibitor, reversed the relaxation induced by 3 mM acetylcholine (ACh) and 2 ± 10 mM Mg 2+ in endotheliumintact (+E) rat aortic rings precontracted with 1 mM phenylephrine (PE). In PE-precontracted endothelium-denuded (7E) rat aorta, 3 mM ACh did not, but Mg 2+ caused relaxation which was reversed by L-NAME, but not by D-NAME. 2 The concentration response pro®les of L-NAME in reversing the equipotent relaxation induced by 5 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The dose of l ‐NAME used was based on previous studies 20,28 and, as previously observed, 20,28 changes in cardiovascular function were consistent with NO synthase inhibition. We cannot, however, exclude the possibility that some of the effects of l ‐NAME that we observed were not related to nitrergic mechanisms 29 . Three‐dimensional ultrasound was chosen to measure gastric emptying because of its superior accuracy over 2D ultrasound, 21 and non‐invasive nature, and because no ionizing radiation is required, unlike scintigraphy 22 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The dose of l ‐NAME used was based on previous studies 20,28 and, as previously observed, 20,28 changes in cardiovascular function were consistent with NO synthase inhibition. We cannot, however, exclude the possibility that some of the effects of l ‐NAME that we observed were not related to nitrergic mechanisms 29 . Three‐dimensional ultrasound was chosen to measure gastric emptying because of its superior accuracy over 2D ultrasound, 21 and non‐invasive nature, and because no ionizing radiation is required, unlike scintigraphy 22 .…”
Section: Discussionmentioning
confidence: 97%
“…We cannot, however, exclude the possibility that some of the effects of L-NAME that we observed were not related to nitrergic mechanisms. 29 Three-dimensional ultrasound was chosen to measure gastric emptying because of its superior accuracy over 2D ultrasound, 21 and noninvasive nature, and because no ionizing radiation is required, unlike scintigraphy. 22 Three-dimensional ultrasound has also been validated against scintigraphy for the measurement of gastric emptying of a liquid meal in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported 3 that 100 μmol/L L ‐NAME reversed the relaxation induced by 3 μmol/L acetylcholine (ACh) and 2–10 mmol/L Mg 2+ in endothelium‐intact (+E) rat aortic rings precontracted with 1 μmol/L PE with a similar IC 50 at equipotent concentrations of ACh and Mg 2+ . In PE‐precontracted endothelium‐denuded (–E) rat aorta, ACh did not, but Mg 2+ did, cause relaxation that was reversed by L ‐NAME, but not by D ‐NAME.…”
Section: Reversal Of Mg2+‐induced Relaxation By L‐name In Endotheliummentioning
confidence: 99%
“…Furthermore, 10 mol/L L-NMMA does not affect basal diameter or basal NO release 37 measured in isolated arterioles and is without nonspecific smooth muscle effects observed at higher concentrations. 38 Nonetheless, our findings prompted experiments to further define the mechanisms by which VEGF 165 caused vasodilation in coronary arterioles from our model. VEGF stimulates production of NO and prostacyclin, which increase vessel permeability, induce endothelial cell proliferation and migration, 30,39,40 and cause vasodilation 25 and hypotension.…”
Section: Vegf 165 -Induced Vasodilation: Role Of Nos and Cyclooxygenasementioning
confidence: 99%